Teo-Ekologi: Bahan Alternatif Pembuatan Ogoh-Ogoh Ramah Lingkungan Untuk Menjaga Kelestarian Budaya Bali - Widyasari, Ida Ayu Putri Genta (Widya Sundaram : Jurnal Pendidikan Seni Dan Budaya, 2025)
This research examines the use of environmentally friendly materials in making Ogoh-ogoh in Bali, focusing on the city of Denpasar. The study aimed to identify challenges and opportunities in transitioning to using environmentally friendly materials, such as bamboo, paper platters, and recycled paper, as a replacement for Styrofoam. The research method was a descriptive qualitative approach, with in-depth interviews and participatory observation of sekaa teruna, Ogoh-ogoh craftsmen, and local government. The results showed that although environmental awareness among Balinese people is high, the main challenge lies in the higher cost and longer processing time with natural materials. Nonetheless, the younger generation has great potential in adopting eco-friendly materials and playing a key role in maintaining the sustainability of Balinese culture. This research also introduces the concept of theo-ecology, which combines the principles of ecology and spirituality in Balinese tradition and makes a new contribution to sustainable cultural management. The conclusions of this study emphasize the importance of more coordinated policies to support the adoption of eco-friendly materials and ensure the preservation of culture and environment simultaneously. These results provide important insights for developing cultural and environmental sustainability science.